USE OF VIDEOGAMES AS LEARNING STRATEGIES IN MEDICAL STUDENTS: A SYSTEMATIC REVIEW - Iván HERNÁNDEZ-PORRAS; Diego-Oswaldo CAMACHO-VEGA; Luis Hernán CARRILLO-VÁRGUEZ (Anthropological Researches and Studies)
Objective: This systematic review aimed to evaluate the relevance of videogame-based strategies in cognitive learning outcomes among the medical students. Methods: Following the PRISMA guidelines, an electronic systematic search was conducted using the Web of Science, PubMed/MEDLINE, EBSCO, and Scopus databases of indexed journals from 2014 to 2024. The search criteria used were: ((“game-based learning” OR “videogames”) AND (“medical education” OR “medical students”) AND (“cognition” OR “education”)). All these studies which has evaluated the use of videogames in medical education as a learning strategy were included. Results: The initial search yielded 125 results, leading to a final selection of 10 studies that met all inclusion criteria and were evaluated using the Physiotherapy Evidence Database (PEDro) scale. From all these key aspects, such as population, Game-Based Learning strategy, study type, objectives, variables, and results, were compiled from these documents. The publication frequency increased after 2021, with Spain contributing the most publications (n = 6). The analysis revealed various videogame-based approaches that generally showed some positive effects on student motivation and cognitive performance. However, several studies had methodological weaknesses, including the small sample sizes and a lack of randomization. Conclusion: This review suggests that video games may improve cognitive learning and motivation among the medical students, although further research is required to confirm this. Future studies should use rigorous designs with larger randomized samples and longer follow-up periods to assess knowledge retention and long-term effects of game-based education.